HEALTH IMPLICATIONS OF WATER SCARCITY IN NIGERIA - Muta’aHellandendu, Joseph (European Scientific Journal, ESJ, 2012)
Nigeria is blessed with abundant water resources but largely untapped. In spite of the abundant water resources, government at all levels (federal, state and local) have not been able to successfully harness these resources to ensure a sustainable and equitable access to safe, adequate, improved and affordable water supply and sanitation to its population. Water and sanitation remain the major primary drivers of public health. Therefore, improving water supply infrastructure will help improve the social well – being of the population directly and better access to portable water can relieve burden of disease as well as the improvements in public health care.